Nephro and hepato protective potential of bacopa phospholipid complex against aluminum- Induced toxicity in rats (Funding Work) - T. MADHAVI; N. JOHN SUSHMA (International Journal of Pharma and Bio Sciences, 2018)
Phytosomes are advanced herbal formulations, binding individual components of herbal extracts to phospholipids resulting in a dosage form that is better absorbed than the conventional herbal extracts. Aluminum is commonly used in daily life, but it can accumulate in mammalian tissues especially brain, bone, liver, kidney and it can be potentially toxic. To examine the protective effect of Bacopa phospholipid complex (BPC) against Aluminum maltolate (AlM) induced nephro and hepato toxicity. Serum aminotransferases, alanine aminotransferase (ALT), aspartate aminotransferase (AST), urea, creatinine, total protein, albumin and lipid profile levels were estimated. Further, tissue alkaline phosphatase (ALP), ALT, AST and architecture of kidney and liver were assessed. AlM administration showed significant increase (P≤0.01) of ALP, ALT, AST, urea, creatinine and decrease in total protein and albumin levels in serum, kidney and liver. Increased levels of total cholesterol, triglycerides and LDL and decreased HDL were also observed with AlM treatment. Degenerative changes observed in kidney’s bowman’s capsule, glomeruli and renal tubules with vacuolization. Dilatation and bleeding areas in liver, vacuolization and degenerative changes in central vein were observed. Whereas synchronous administration of Bacopa monniera (Bm) and BPC with AlM showed significant (P≤0.01) decrease ALP, ALTAST, urea, creatinine and increase in total protein and albumin levels in serum and in tissues were observed. Tissue damage induced by AlM was reduced in AlM+Bm and AlM+BPC groups. Compared to Bm, BPC showed better therapeutic activity. Bm and BPC reduces hepatic and renal damage induced by AlM. Novel formulation of Bm with phospholipids showed increased absorption and enhanced bioavailability of BPC compared to Bm alone.